Polypseudophakia: from "Piggyback" to supplementary sulcus-fixated IOLs - Khoramnia, Ramin; Kahraman, Guenal; Amon, Michael; Łabuz, Grzegorz; Baur, Isabella; Auffarth, Gerd U. (Graefe's archive for clinical and experimental ophthalmology, 2025)
Polypseudophakia, the concept of using a second intraocular lens (IOL) to supplement an IOL that has already been placed in the capsular bag, was first used as a corrective measure where the power requirement was higher than that of available single IOLs. Subsequently, the technique was modified to compensate for post-operative residual refractive errors. In these early cases, an IOL designed for the capsular bag would be implanted in the sulcus. Although these approaches were less than ideal, alternative means of correcting residual refractive errors were not without their limitations: IOL exchange can be traumatic to the eye and is not easily carried out once fibrosis has occurred, while corneal refractive surgical techniques are not suitable for all patients. Piggyback implantation was the term first coined to describe the use of two IOLs, placed together in the capsular bag. The term was later extended to include the procedure where an IOL designed for the capsular bag was placed in the sulcus. Unfortunately, the term piggyback has persisted even though these two approaches have been largely discredited. Intraocular lenses are now available which have been specifically designed for placement in the ciliary sulcus. As these newer IOLs avoid the many unacceptable complications brought about by both types of earlier piggyback implantation, it is time to employ a new terminology, such as supplementary IOL or secondary enhancement to distinguish between the placement of an unsuitable capsular bag IOL in the sulcus and the implantation of an IOL specifically designed for ciliary sulcus implantation. In addition to minimising possible complications, supplementary IOLs designed for the sulcus have expanded the options available to the ophthalmic surgeon. With these new IOLs it is possible to correct presbyopia and residual astigmatism, and to provide temporary correction of refractive errors in growing, or unstable, eyes. This article aims to review the literature available on supplementary IOL implantation in the ciliary sulcus and to summarise the evidence for the efficacy and safety of this intervention.